Sustainable e-commerce strategy as an alternative to preserve indigenous crafts - Seijas-Díaz, José; Martell-Alfaro, Karla; Ruiz-Cueva, John; Sanchez-Castro, Angélica; Barbachán-Ruales, Enrique; Sánchez-Colina, Roberto (Data and Metadata, 2025)
Due to the limitations of handicraft trade in indigenous communities, we propose an e-commerce strategy as an alternative for preservation. The research adopted an ethnographic approach focused on understanding the economic dynamics of handicraft trade in four Shawi indigenous communities in the Peruvian Amazon. The e-commerce strategy is based on four fundamental pillars: brand, product, team, and marketing. Each pillar includes components that must be developed in a structured and coordinated manner to ensure the sustainability of the marketing process of indigenous handicrafts. The study presents an innovative approach by proposing a sustainable e-commerce strategy specifically designed for indigenous handicrafts.